Sharing nature's interest - "Chambers, Nicky" (London, 2006)
Ecological foot printing is rapidly being adopted as an effective and practical way to measure our impact on the environment - in both large- and small-scale planning and development. This is an introduction to ecological footprint analysis, showing how it can be done, and how to measure the footprints of activities, lifestyles, organizations and regions. Case studies illustrate its effectiveness at national, organizational, individual and product levels.
Keywords: Ecology-Sustainable aspects